Development and Standardisation of Cultural Intelligence Scale - Singh, Shireesh Pal; Gangwar, Sumit (JOURNAL OF INDIAN EDUCATION, 2023)
The Cultural Intelligence Scale is a tool that explores how to measure an individual’s ability to understand, act, and manage efficiently in culturally diverse settings. The authors of this paper conducted a study to develop a framework for culturally responsive pedagogy. Culturally responsible pedagogy is a pedagogy that reorganises the students’ knowledge, backgrounds, language, family structure, and social or cultural differences to acknowledge the psychological fact that all learners learn differently. The first objective for developing a framework of culturally responsive pedagogy was to explore the cultural intelligence of teachers and the patterns of culturally responsive pedagogy adopted by them in culturally diverse schools. For exploring the cultural intelligence of teachers, the Cultural Intelligence Scale was developed and standardised, and the procedure for standardisation is presented in this paper. For the development of the Cultural Intelligence Scale, the primary draft of the scale was prepared by the researchers after studying the material available for the scale in which 69 items were placed under four dimensions. All these items were constructed on Likert’s five-point rating scale. The primary draft of the scale was administered to 400 teachers to collect data. After qualitative and quantitative evaluation of the collected data, the final draft of the Cultural Intelligence Scale, consisting of 42 items was prepared after determining the reliability and validity of the scale.